HIDDEN DEBT CHINA KE INDONESIA MASA PANDEMI COVID-19: TINJAUAN ATAS PERSPEKTIF STRUKTURALIS DAN RATIONAL CHOICE THEORY - Fuad Azmi; Emil Mahyudin; Gilang Nur Alam; RMT Nurhasan Affandi; Windy Dermawan (Media Bina Ilmiah, 2022)
Covid 19 has an impact on the world economic crisis which has brought the world to the brink of the worst economic recession in the last 50 years of world economic history. This causes the state to require debt to other countries, including Indonesia. Indonesia's state debt during the pandemic continued to grow so that it was accused of "Hidden Debt" to the Chinese state from both government and non-government. Foreign debt is not a secret matter, but the state must owe it to survive. The theory used in this paper is Structuralism Theory and Rational Choice. This paper finds that hidden traps in the short term are a source of stimulus for the recovery of the economic and infrastructure sectors in Indonesia after Covid-19, but in the long term it has the potential to cause problems for Indonesia's dependence on China and a threat to economic independence. Therefore, Indonesia needs to compile a roadmap regarding economic recovery after the Covid-19 pandemic by utilizing potential foreign sources to be developed and in the nature of cooperation.